Unveiling mortality predictors: Exploring phase angle as a prognostic indicator in adult and elderly patients on home enteral nutrition in curitiba - Paola Pasini Vicenski; Janaina Bach Naslowski; Estela Iraci Rabito; Maria Cristina Gonzalez; Maria Eliana Madalozzo Schieferdecker (Clinical Nutrition Open Science)
Summary: Background and Aims: This study investigated the Standardized Phase Angle (SPA) as a prognostic indicator of mortality among individuals undergoing Home Enteral Nutrition (HEN). Methods: We conducted an observational, analytical, longitudinal study involving 108 HEN participants. Body composition was assessed using bioelectrical impedance analysis, with reactance and resistance values utilized to estimate PA. Following adjustments for age and sex, SPA was derived. Clinical outcomes such as recurrence or death were ascertained by contacting patients or caregivers via telephone 90 days post initial home visit. We examined the association between SPA, disease, and mortality outcome. Results: The majority of patients were elderly, with a mean age of 68.8 years, predominantly male (56.5%), and afflicted with neurological diseases (70.4%). SPA yielded a negative value in 88.9% of the sample. A high SPA value indicated greater protection (OR 0.50, CI 0.28–0.89, P = 0.0181). Males exhibited lower SPA values compared to females (-2.9 vs. -1.8, P < 0.0001). Patients with cancer had a 492% higher likelihood of mortality compared to those with neurological diseases (OR 5.92, CI 1.23–28.46, P = 0.0263). The ROC curve demonstrated that the optimal SPA cutoff for identifying mortality risk was -2.6°. Conclusions: SPA has emerged as a predictive tool for mortality in patients with HEN. SPA can be used as a complementary tool in the general nutritional assessment of this population.